Study on preparation of hydrotalcite based catalyst containing Mg-Al-Co compositions. - Diệu Hồng, Nguyễn Khánh; Hùng, Nguyễn Văn; Thành, Nguyễn Trung (Vietnam Journal of Chemistry, 2017)
A series of hydrotalcite based materials containing Mg-Al-Co compositions were synthesized through co-condensation method using corresponding metallic salts as precursors in alkaline environment. Many parameters such as molar ratios of the precursors, temperature and time were investigated to clarify effects of them on the co-condensation reactions. The as-synthesized material obtained from the chosen parameters was calcined at different temperature such as 200, 300, 400 and 500 oC for estimating its thermal stability. Some techniques were applied including XRD and SEM for characterizing the prepared materials. Keywords. Hydrotalcite, brucite, co-condensation, layer double hydroxides.